SMG231 : Introduction to sports reporting / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation
This course is designed to introduce and expose students to the basic principle of communication in a sports environment. It will provide students with knowledge of communicating successfully in their personal, social and workplace interaction. The subject will also expose students to learn the fundamental skills needed to create sports content across all media platforms. Beyond the technical aspects of reporting and writing, the student will learn to think more critically about what it means to be a sports journalist today in the evolving world of sports media